Developing standards for good educational assessment of handwriting الإبداع في إتقان مهارات الخط العربي في العصر الرقمي - Heba Tawfiqe Abu Eyadah (Universitas Negeri Malang, 2024)
ABSTRACT The current study aims to identify ways of innovation and creativity in mastering Arabic calligraphy skills in the digital age by investing in the digital revolution, artificial intelligence applications, and the outcomes of the Fourth Industrial Revolution to improve and enhance calligraphy, to come up with proposals and procedures that help enable writing skills, master calligraphy, and enable individuals to be creative in calligraphy, through analyzing and reviewing previous research, studies, and educational literature that dealt with Arabic calligraphy. The current study differs from previous studies in its study methodology, as the current study relies on analyzing educational literature that discussed the topic of Arabic calligraphy and ways of creativity, innovation, and developing its skills through the analytical inductive approach. In light of the results of previous studies and according to the researcher's vision, the current study presents a set of recommendations.. تهدف الدراسة الحالية تعرُف سبل الابتكار والإبداع في إتقان مهارات الخط العربي في العصر الرقمي من خلال استثمار الثورة الرقمية وتطبيقات الذكاء الاصطناعي ونتاجات الثورة الصناعية الرابعة لتحسين وتجويد الخط، للخروج منها بالمقترحات والإجراءات التي تساعد على تمكين مهارات الكتابة وإتقان الخط وتمكين الأفراد من الإبداع في الخط، من خلال تحليل ومراجعة البحوث والدراسات السابقة والأدبيات التربوية التي تناولت الخط العربي. وتختلف الدراسة الراهنة عن الدراسات السابقة في منهجية الدراسة إذ تعتمد الدراسة الحالية على تحليل الأدبيات التربوية التي تداولت موضوع الخط العربي وسبل الإبداع والابتكار وتنمية مهاراته من خلال المنهج التحليلي الاستقرائي وفي ضوء نتائج الدراسات السابقة ووفقًا لرؤية الباحث تقوم الدراسة الراهنة بتقديم جملة توصيات.